A platform for automated manufacturing system analysis and design - Gao, Qing (2009)
This thesis presents a useful methodology to represent, process and translate knowledge in a hybrid rule-based expert Petri net(TREPN) system. It provides a platform for general users untrained in the knowledge of Petri nets to design an automated manufacturing system (AMS) easily through the interaction of the friendly user interface of RBES and automatically evaluate the designed model through the graphical and dynamic analysis of the Petri nets.